Early establishment of Suaeda salsa population as affected by soil moisture and salinity: Implications for pioneer species introduction in saline-sodic wetlands in Songnen Plain, China. (December 2019) - An, Yu; Gao, Yang; Zhang, Yang; Tong, Shouzheng; Liu, Xiaohui
Highlights: Effects of soil moisture, salinity, and alkalinity on Suaeda salsa population were investigated. Relationships among soil moisture, EC and pH in saline-sodic wetlands were observed. Soil moisture and EC were major determinants for earlier establishment of S. salsa population. Root/shoot ratio of S. salsa was in positive correlation with soil moisture and salinity. Abstract: Due to the combined influences of climate change and human activities, the water deficiency and saline-alkalinization of soil are becoming more severe in the Momoge National Nature Reserve (MNNR) in Songnen Plain, China, resulting in extensive vegetation degradation in wetlands. Suaeda salsa acts as a pioneer species in vegetation restoration of saline-sodic wetlands in MNNR because of its high salt-tolerance. The seeding emergence and early growth of S. salsa in natural condition can be especially affected by the increased water, salt, and alkaline stresses in the surface soil. However, little is known about the plant-soil relations, as it leads to the uncertainty of establishing S. salsa population in degraded wetlands. The purpose of the present study is to quantify the main soil factors controlling the early establishment of S. salsa population. The heterogeneity in soil water content (SWC), electrical conductivity (EC) and pH across 0–20 cm soil, and S. salsa population characteristics were investigated in natural stands, as well as their relationships were studied. There was a synergistic relationship between EC and pH across 0–20 cm soil, and they had negative correlation with SWC in 5–20 cm soil, implying that the water management could potentially affect soil saline-alkalinization. Redundancy analysis and correlation analysis revealed that the S. salsa characteristics were negatively related with SWC in 0–10 cm and EC in 0–5 cm soil, demonstrating that soil moisture and salinity in surface soil were major determinants of early establishment of S. salsa population. In addition, the positive relationships between the root/shoot ratio (RSR) and SWC and EC in 0–5 cm soil indicated that S. salsa adapted to the increased moisture and salinity by regulating the biomass allocation between shoot and root. Results in this study suggest that soil moisture and salinity can be used as effective environmental indicators for evaluating the early establishment of S. salsa population during pioneer species introduction for vegetation restoration in degraded saline-sodic wetlands in Songnen Plain.